Evaluation of the IMF's Role in Poverty Reduction Strategy Papers and the Poverty Reduction and Growth Facility - International Monetary Fund; Independent Evaluation Office, International Monetary Fund (Washington D.C.: International Monetary Fund, Independent Evaluation Office, 2004)
The evaluation has focused on intermediate stage outcomes, that is, the quality of the broader based policy formulation process, the nature of the strategy and policy framework that has evolved interaction between this framework and the PRGF and the effectiveness of the IMF's role. The authors summarized their major findings, as well as the lessons to be drawn from them, and make a number of recommendations for the future. The final section reflects on some implications of the evaluation for the longer term role of the IMF in low-income countries.
Includes bibliographical references.
rpm 18/09/13
Loans
Keywords: International Monetary Fund; Developing countries; Poverty